Survival analysis following microwave ablation or surgical resection in patients with hepatocellular carcinoma conforming to the Milan criteria - Sun, Quan (Oncol Lett, 2020)
The aim of the present study was to compare the efficacy of microwave ablation (MWA) and surgical resection (RES) for the treatment of hepatocellular carcinoma (HCC) conforming to the Milan criteria and the associated short- and long-term survival rates. The baseline characteristics were obtained from 231 patients with HCC who met the Milan criteria. To compare the mortality rates between groups, survival analysis was conducted using the Kaplan-Meier method and the log-rank test. The factors associated with the survival rate were analyzed using Cox proportional hazard models. A total of 115 patients underwent RES, and 116 were treated with MWA. No significant differences were observed in the 1-, 3- and 5-year OS rates and the 1-year DFS rate between the two groups. The 7- and 10-year OS rates and the 3-, 5-, 7- and 10-year DFS rates of the RES group were significantly higher compared with those in the MWA group (P=0.004, P=0.002, P=0.003 and P=0.002, respectively). In addition, no marked differences were observed in the OS and DFS rates between the two groups of patients with solitary HCC lesions ≤3 cm (P=0.066 and P=0.056) and in the OS of those with solitary lesions of 3–5 cm (P=0.133); however the DFS of patients with single 3–5 cm HCC lesions in the RES group was notably higher compared with the MWA group (P=0.027). The Cox proportional hazard model revealed that age, hepatitis B and C virus infection, tumor size, number, platelet count and the type of treatment intervention were risk factors affecting the survival and recurrence in patients with HCC. These results suggested that RES may provide superior survival benefits compared with MWA for patients with HCC who meet the Milan criteria.